Cystic Duodenal Duplication in a Cat - Souza Brito, Yane; Rodrigues Ribeiro, Rafaela; Vieira Costa, Daniel; Alves Arantes, Ana Paula; Félix Solareviscky, Victor; Meneses de Castro, Lara; Martins Oliveira, Iago (Acta Scientiae Veterinariae, 2025)
Background: Cystic duodenal duplication in felines is a rare congenital malformation. Although well-documented in humans and other animal, such as dogs and cats, its occurrence is rare in felines. Clinically, this condition manifests as cysts containing histological structures similar to the gastrointestinal tissue, which can be found at different levels of the digestive tract. Thus, this case report aimed to describe the main aspects of cystic duodenal duplication, its clinical symptoms, its diagnostic methods, and its treatment options. Case: A 8-month-old neutered, female cat, weighing 2.5 kg, was attended for clinical evaluation. Major complaints reported by the guardian were weight loss and constant emesis, with presence of bile and as many as 8th episodes in a day. During the physical examination, no changes in vital parameters were observed. Laboratory tests such as blood count, biochemistry, histopathology, and abdominal ultrasound were performed, revealing a tubular, homogeneous anechoic structure approximately 2.51 cm in length and adjacent to the duodenal serous/muscular layer. For a definitive diagnosis, histopathological analysis of the structure observed during the imaging exam was requested. The patient was then referred to the surgical ward and underwent exploratory celiotomy. An oval-shaped cystic structure with a serous appearance adhered to the duodenal-pancreatic section was dissected, stored in 10% buffered formalin, and sent for histopathological analysis. Results were suggestive of cystic enteric duplication, with lesion margins comprising a muscular layer and inflammatory cells. Discussion: Cystic duodenal duplication is a congenital malformation accounting for approximately a 3rd of the duplications occurring in the gastrointestinal tracts of cats. However, there are more reports describing these cysts in dogs than in cats. The aggravating factor in cats and dogs tends to be partial or total obstruction of the duodenum, which may or may not be associated with tenesmus. Furthermore, although rare, duplication cysts of the gastrointestinal tract, characterized by embryological malformations, cause important clinical signs, such as emesis and anorexia, corroborating what was observed in this case. These are important for the differential diagnosis of animals with chronic gastrointestinal signs, and those that do not respond to pharmacological therapy. Duplication cysts are characterized considering 3 main criteria. They must be associated with the gastrointestinal tract, and they must have a muscular layer and epithelium similar to that of the gastrointestinal tract on histopathological analysis. Moreover, its presentation on ultrasound is usually associated with the formation of a rim sign by the hypoechoic muscle layer along with the serosa with greater echogenicity and an anechoic center due to the presence of fluid. Herein, only a homogeneous anechoic structure was observed on ultrasound, and histopathological examination revealed a structure compatible with cystic enteric duplication associated with inflammatory cells. Therefore, it is crucial not to rule out the diagnosis of an enteric duplication cyst on the basis of ultrasound solely, as this is an auxiliary method of diagnosis, and is used to plan surgical approaches. Keywords: feline, enteric duplication cyst, duodenum. Título: Duplicação duodenal cística em gato Descritores: felino, cistos de duplicação entérica, duodeno.